AKAD MURABAHAH AND IJARAH AND THEIR APPLICATION IN ISLAMIC FINANCIAL INSTITUTIONS - A.Habibi A; Syufa’at (LPPM, Universitas Muhammadiyah Riau, 2024)
The increase in people's needs is hampered by busyness and inability to meet their needs so that people need alternatives to help them fulfill their needs. Sharia Financial Institutions (LKS) have emerged as an alternative for people to meet their needs. The main product that LKS offers to the public is murabahah because there is little risk in its application. However, the murabahah application has caused a lot of criticism among the public. Islamic banks are often referred to as